Solvent Isotope Effect on Transfer Hydrogenation of H2O with Glycerine under Alkaline Hydrothermal Conditions - Shen, Zheng; Gu, Minyan; Liu, Shiyang; Dong, Wenjie; Zhang, Yalei (Journal of Technology Innovations in Renewable Energy, 2014)
Solvent isotope effect was investigated with 1H-, 2H-NMR, LC-MS and Gas-MS analyses on transfer hydrogenation of H2O with glycerine under alkaline hydrothermal conditions. The results from solvent isotope studies showed that (1) the H on the β-C of lactate was almost exchanged by D2O, which suggests that the hydroxyl (-OH) group on the 2-C of glycerine was first transformed into a carbonyl (C=O) group and then was converted back into a -OH group to form lactate; (2) The presence of large amounts of D was found in the produced hydrogen gas, which shows that the water molecules acted as a reactant; and (3) D% in the produced hydrogen gas was far more than 50%, which straightforwardly shows that acetol was formed in the first place as the most probable intermediate by undergoing a dehydration reaction rather than a dehydrogenation reaction.